Contemporary Challenges and Legal Resolutions in the Implementation of Accessibility Rights for Persons with Disabilities in Indonesia - Rohmah Ageng Mursita (Islamic Research Publiser, 2024)
This study examines the contemporary challenges and legal solutions to implementing accessibility rights for persons with disabilities in Indonesia. It aims to evaluate the level of accessibility across public facilities and analyse the effectiveness of existing legal frameworks, including Law No. 8 of 2016 on Persons with Disabilities and its derivative regulations. Using a qualitative approach that integrates literature review, legal framework analysis, and case study assessment, the research explores how national laws are applied at the local level and identifies the factors that hinder inclusivity in public spaces. The findings reveal that, despite the presence of comprehensive legal protections, significant implementation gaps persist. Many public spaces, educational institutions, and workplaces fail to meet accessibility standards, particularly affecting individuals with mobility and sensory impairments. Barriers are both social and physical, including limited public awareness, inadequate infrastructure such as ramps and sidewalks, weak institutional coordination, and insufficient monitoring mechanisms. Furthermore, local governments often lack the technical capacity and financial resources to enforce accessibility regulations effectively. To address these issues, this study proposes several legal and policy recommendations: (1) strengthening the enforcement of accessibility laws and local regulations; (2) prioritising funding and training for inclusive infrastructure development; (3) promoting intersectoral collaboration among government institutions, disability organisations, and communities; and (4) enhancing public awareness about disability rights and inclusive design. Academically, this research contributes to the discourse on human rights and inclusive law by emphasising the need for a rights-based, participatory, and contextually responsive legal approach to disability inclusion in contemporary Indonesia.